2017
DOI: 10.1186/s12886-017-0639-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orthokeratology on myopia progression: twelve-year results of a retrospective cohort study

Abstract: BackgroundSeveral studies reported the efficacy of orthokeratology for myopia control. Somehow, there is limited publication with follow-up longer than 3 years. This study aims to research whether overnight orthokeratology influences the progression rate of the manifest refractive error of myopic children in a longer follow-up period (up to 12 years). And if changes in progression rate are found, to investigate the relationship between refractive changes and different baseline factors, including refraction err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 45 publications
0
63
0
6
Order By: Relevance
“…This dramatic initial visual improvement is consistent with previous studies. [15,16] The initial correction achieved in the morning after overnight OKwear starts wearing off within hours due to the regression of the corneal shape, leading to visual blurring in the afternoon period. [13] This fact was confirmed by our results, with patients complaining of afternoon blur with a drop of 1.2 Snellen lines in the evening during the first week.…”
Section: Discussionmentioning
confidence: 99%
“…This dramatic initial visual improvement is consistent with previous studies. [15,16] The initial correction achieved in the morning after overnight OKwear starts wearing off within hours due to the regression of the corneal shape, leading to visual blurring in the afternoon period. [13] This fact was confirmed by our results, with patients complaining of afternoon blur with a drop of 1.2 Snellen lines in the evening during the first week.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that orthokeratology can control myopia for up to 8 years. 15,16 However, other studies reported that the time-dependence of using OK lenses significantly reduced the efficacy of their myopic controls. It was confirmed that even without OK lenses, the diopters of myopic children would drop, which is a natural process.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to stronger compliance with adolescent women compared to men, which led to better outcomes. 15,22…”
Section: Discussionmentioning
confidence: 99%
“…Longer retrospective studies have been published reporting myopia progression in children wearing orthokeratology lenses. A study by Downie and Lowe reported that orthokeratology slowed myopia progression for up to eight years, while another study by Lee et al reported significantly slower myopia progression in children wearing orthokeratology lenses up to six years after the start of treatment. One limitation of both studies, apart from the fact that they were retrospective record reviews, is that both studies measured myopia progression by over‐refraction over the orthokeratology lenses as opposed to measuring changes in axial length.…”
Section: Myopia Controlmentioning
confidence: 99%